Not the End of Everything, but the Beginning of Salvation for All Creation: A Historical Interpretation of Revelation 21:1-8 - Sirait, Jeremy Georgias; Sitorus, Herowati (Program Pascasarjana UKIM, 2025)
This article discusses the Book of Revelation, which is often perceived as a frightening book due to its abundance of apocalyptic symbols and confusing, terrifying end-time narratives. Such interpretations have caused fear and confusion, particularly among modern readers, regarding the concept of the end times. This article addresses this issue with the aim of re-examining the core message of Revelation by analyzing Revelation 21:1–8. This passage is understood as the climax of the revelation, emphasizing God’s promise of salvation and renewal. The method used in this study is a literature review combined with a historical-critical exegetical approach to explore both the historical context and the theological meaning of the text. The findings reveal that Revelation 21:1–8 presents an eschatological vision filled with hope, affirming that salvation is the central message of the Book of Revelation. Therefore, although the book begins with seemingly frightening symbols and narratives, readers should not remain trapped in fear. Instead, they are encouraged to understand the entire book as a progressive unveiling of God's love and salvation for humanity. In this way, the end times should no longer be seen as a terrifying event, but rather as the beginning of the salvation that God offers to humankind.